Effects of Dietary Antimicrobial Growth Promoters on Performance Parameters and Abundance and Diversity of Broiler Chicken Gut Microbiome and Selection of Antibiotic Resistance Genes - Paul, Shyam Sundar; Rama Rao, Savaram Venkata; Hegde, Nagendra; Williams, Nicola J.; Chatterjee, Rudra Nath; Raju, Mantena Venkata Lakshmi Narasimha; Reddy, Godumagadda Narender; Kumar, Vikas; Phani Kumar, Prakki Santosh; Mallick, Sathi; Gargi, Madhuranjana (Frontiers in Microbiology, 2022)
Antimicrobial growth promoters (AGP) are commonly used in broiler production. There is huge societal concern around their use and their contribution to the proliferation of antimicrobial resistance (AMR) in food animals and dissemination to humans or the environment. However, there is a paucity of comprehensive experimental data on their impact on poultry production and the AMR resistome. Here we investigated the effect of five antimicrobial growth promoters (virginiamycin, chlortetracycline, bacitracin methyl disalicylate, lincomycin, and tylosin) used in commercial broiler production in the Indian subcontinent and different parts of the world for three consecutive production cycles on performance variables and also the impact on gut bacteria, bacteriophage and resistome profile using culture-independent approaches. There was no significant effect of AGPs on cumulative growth or feed efficiency parameters at the end of the production cycles and cumulative mortality rates were also similar across groups. Many antibiotic resistance genes (ARGs) were ubiquitous in the chicken gut irrespective of AGP supplementation. In total, 62 ARGs from 15 antimicrobial classes were detected. Supplementation of AGPs influenced the selection of several classes of ARGs, however, this wasn’t correlated necessarily with genes relevant to the AGP drug class; some AGPs favored the selection of ARGs related to antimicrobials not structurally related to the AGP. AGPs did not appear to impact the gut bacterial community structure, including alpha or beta diversity significantly, with only 16-20 operational taxonomic units of bacteria being altered significantly. However, several AGPs significantly reduced the population density of some of the potential pathogenic genera of bacteria such as E. coli. Chlortetracycline increased the abundance of Escherichia phage, whereas, other AGPs did not influence the abundance of bacteriophage significantly. Considering the evidence that AGPs used in poultry production can select for resistance to more than one class of antimicrobial resistance, and the fact that their effect on performance is not significant their use needs to be reduced and there is a need to monitor the spread of ARGs in broiler chicken farms.